GAMBARAN PENDAPAT KELUARGA ORANG DENGAN GANGGUAN JIWA (ODGJ) TENTANG PENYEBAB TERJADINYA GANGGUAN JIWA DAN PENGOBATANNYA PADA MASYARAKAT MELAYU - Megawati, Megawati; Nauli, Fathra Annis; Hasanah, Oswati (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022, 2022)
Mental disorders are influenced by two factors, namely predisposing factors and precipitation factors. This study aims to determine the description of the family of People with Mental Disorders (ODGJ) about the causes of mental disorders and their treatment in the Malay community in the Meranti Islands. This study used a quantitative descriptive design on 30 respondents using a total sampling technique, and the instrument used in this study was a questionnaire. The results of the univariate analysis of the majority of respondents aged 17-25 years (26,7%), the majority of respondents were female (80%), the majority of respondents had high school education (36,7%), most worked as IRT (46,7%). The main genetic predisposition of respondents is that no family member has mental disorders (86,7%), the majority of respondents have psychosocial disorders (28,9%), the majority of respondents have an unpleasant past history of physical violence (23,5%). The type of treatment most of the respondents did informal treatment (63,3%). Predisposing factors for ODG are caused by biology, psychology and socio-culture, while the treatment that is often used is doing informal treatment (shaman and ustad).